Ultrahigh-strength and high-toughness Fe-Mn-Ni series alloy and preparation method thereof

By accurately designing the chemical composition and heat treatment process of Fe-Mn-Ni alloys, the ultrasonic mixing method and gas compressor are used to perform thermal isostatic pressure treatment to form a uniform microstructure, solving the problem of insufficient reliability and durability of the alloy in extreme environments, and achieving high strength and high toughness effects.

CN119800202AActive Publication Date: 2025-04-11YANTAI LIYUANLI MASCH PARTS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411964275.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-04-11
Estimated Expiration
2044-12-30

AI Technical Summary

Technical Problem

Fe-Mn-Ni system alloys have problems such as phase change behavior and balance of precipitation strengthening and toughness in element ratio and heat treatment processes, resulting in insufficient reliability and durability of the materials in extreme environments.

Method used

By accurately designing the chemical composition and heat treatment process of Fe-Mn-Ni alloys, the ultrasonic mixing method and gas compressor are used for thermal isostatic pressure treatment, combined with solid solution treatment and hot extrusion process, a uniform microstructure is formed to improve the strength and toughness of the material.

Benefits of technology

It significantly improves the hardness, toughness and tissue uniformity of Fe-Mn-Ni alloy, maintains good forming ability and mechanical stability, and is suitable for applications in high stress and low temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119800202A_ABST
    Figure CN119800202A_ABST
Patent Text Reader

Abstract

The invention relates to an ultrahigh-strength and high-toughness Fe-Mn-Ni series alloy and a preparation method thereof, and belongs to the technical field of alloy materials. Comprising the following steps: step 1, preparing the following chemical components in percentage by mass: 91.2% of Fe, 2.8% of Mn, 5.7% of Ni and 0.3% of C metal powder, mixing by adopting an ultrasonic mixing method, separating a medium by adopting a natural sedimentation method, and drying the powder in a drying oven; 2, the dried powder is placed in a gas compressor to be subjected to hot isostatic pressing treatment, smelting is conducted in the helium gas environment, and a Fe-Mn-Ni series alloy cast ingot is obtained; 3, the cast ingot is subjected to solution treatment; 4, the cast ingot obtained after solution treatment is subjected to hot extrusion, and an alloy cast ingot is obtained; through precise component design and optimization of a heat treatment process, the hardness, toughness and structure uniformity of the Fe-Mn-Ni alloy are remarkably improved, and meanwhile good forming capacity and mechanical stability are kept.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an ultra-high-strength and high-toughness Fe-Mn-Ni alloy and a preparation method thereof, and belongs to the technical field of alloy materials. Background Art

[0002] Low manganese steel has attracted wide attention due to its low manganese content (usually less than 1.65%) and high strength and toughness. This steel is based on carbon structural steel and optimizes its performance by adding appropriate amounts of other alloying elements (such as silicon, chromium, nickel, etc.), which can meet the diverse needs of construction, automobiles, bridges, energy and other fields. Although the reduction of manganese content in low manganese steel helps to reduce costs and improve processing performance, it may also lead to insufficient material strength and reduced toughness.

[0003] In recent years, high-strength and toughness Fe-Mn-Ni alloys have become a research hotspot due to their potential application value in extreme environments. For example, this system of alloys can be used in high-strength and low-temperature storage tanks, wear-resistant engineering machinery, and key components in corrosive environments. Compared with traditional high-manganese steel and ordinary low-manganese steel, this type of alloy can achieve a better match between strength and toughness, and has excellent reliability and durability in high stress and low temperature environments.

[0004] However, the development of Fe-Mn-Ni system alloys requires solving a series of technical problems. The first is the influence of element ratio on phase transformation behavior. Changes in manganese and nickel content will not only affect the microstructure evolution of the alloy, such as the stability of austenite and martensite, but will also significantly change the deformation mechanism of the material (such as twinning and slip); the second is the balance between precipitation strengthening and toughness. By reasonably designing the alloy composition and heat treatment process, stable and fine second phase particles can be formed in the alloy, thereby effectively improving the material strength. However, if the particles are unevenly distributed or excessively precipitated, it may cause toughness degradation.

[0005] Therefore, it is necessary to design an ultra-high strength and high toughness Fe-Mn-Ni alloy and its preparation method that can achieve industrial preparation, process optimization and long-term performance stability. Summary of the invention

[0006] In view of the deficiencies in the above-mentioned prior art, the present invention provides an ultra-high-strength and high-toughness Fe-Mn-Ni alloy and a preparation method thereof.

[0007] The technical solution of the present invention to solve the above technical problems is as follows:

[0008] An ultra-high-strength and high-toughness Fe-Mn-Ni alloy and a preparation method thereof, comprising the following steps:

[0009] Step 1, the ingredients are prepared according to the following chemical composition and mass ratio, the mass percentage of the metal powders of Fe, Mn, Ni and C elements is: Fe 91.2%, Mn 2.8%, Ni 5.7%, C 0.3%, ultrasonic mixing method is used for mixing, natural sedimentation method is used for separating the medium, and the powder is placed in an oven for drying;

[0010] Step 2: placing the dried powder in a gas compressor for hot isostatic pressing, and smelting the powder in a helium gas environment to obtain a Fe-Mn-Ni alloy ingot;

[0011] Step 3, subjecting the ingot to a solution treatment;

[0012] Step 4, hot extruding the solution treated ingot to obtain an alloy ingot;

[0013] Step 5: The alloy ingot after hot extrusion treatment is kept in a muffle furnace at 750° C. for 10 minutes and then air-cooled to room temperature; it is kept in a salt bath furnace at 150° C. for 30 minutes and then air-cooled to room temperature to obtain an ultra-high strength and high toughness Fe-Mn-Ni alloy.

[0014] Furthermore, in step 1, the purity of Fe, Mn, Ni and C powders is higher than 99.95%.

[0015] Furthermore, in step 1, the average particle diameter of Fe, Mn, Ni, and C metal powders is controlled to be between 50 and 100 μm through a screening process.

[0016] Furthermore, in the step 1, when mixing by ultrasonic mixing, the ratio of powder mass to deionized water liquid is 10:1, the ultrasonic processor is set to a power of 350 W and a frequency of 40 kHz, and a pulse mode treatment is performed for 30 minutes. The liquid temperature should be controlled at 50°C. After the mixing is completed, the powder is allowed to stand for one day by natural sedimentation, the powder deposited at the bottom is collected, the upper clear liquid is absorbed, and finally dried in an oven at 120°C for 2 hours.

[0017] Furthermore, in the step 2, hot isostatic pressing is carried out in a temperature range of 1000°C-1100°C, a heating rate of 10°C / s, an applied pressure of 120MPa, a pressing time of 30 minutes, and a holding time of 2 hours; during the pressing process, the temperature and pressure need to be evenly transmitted to ensure the densification effect; after the treatment, the temperature is slowly lowered at a cooling rate of 10°C / min to finally obtain a Fe-Mn-Ni alloy ingot.

[0018] Furthermore, the grain size and structural uniformity of the Fe-Mn-Ni alloy ingot obtained in step 2 are detected by optical microscopy and XRD analysis to ensure that the subsequent processing requirements are met.

[0019] Furthermore, in step 3, the ingot is kept at 1200° C. for 90 minutes to complete the solution treatment.

[0020] Furthermore, in step 4, the solution treated material is hot extruded in a temperature range of 900° C. to 1000° C., the pressure applied during extrusion is 1000 MPa, and the extrusion speed is controlled at 5 mm / s.

[0021] Furthermore, in step 4, after extrusion is completed, cooling is performed at a rate of 10° C. / min.

[0022] An ultra-high-strength and high-toughness Fe-Mn-Ni alloy is prepared by the above-mentioned method for preparing the ultra-high-strength and high-toughness Fe-Mn-Ni alloy.

[0023] The beneficial effects of adopting the above further scheme are: through precise composition design and optimization of heat treatment process, the hardness, toughness and structural uniformity of Fe-Mn-Ni alloy are significantly improved, while maintaining good forming ability and mechanical stability;

[0024] The solution treatment is completed by keeping the ingot at 1200℃ for 90 minutes. At this temperature, the alloy elements (such as Mn, Ni, and C) are fully dissolved into the matrix, and the segregation phenomenon in the cast structure is effectively eliminated. Element segregation often exists in the cast material, which may lead to uneven material properties and affect the quality and reliability of subsequent processing. The solution treatment at 1200℃ not only helps to dissolve the alloy elements in the raw materials, but also eliminates the coarse grain structure and makes the material structure more uniform.

[0025] The gas compressor can achieve densification of powder materials, elimination of pores and homogenization of microstructure through the uniform transmission of high-temperature and high-pressure inert gas. It can maintain the geometric integrity of the material while applying isotropic pressure, avoid uneven deformation or internal stress, and effectively improve the mechanical properties and reliability of the alloy.

[0026] Reference numerals

[0027] Figure 1 It is a hardness diagram of the sample of the present invention under different heat treatment methods;

[0028] Figure 2 It is a hardness diagram of the sample of the present invention under different heat treatment methods;

[0029] Figure 3 The engineering stress-strain curves of the samples of the present invention under different heat treatment modes;

[0030] Figure 4 -a is a 2000 times fracture morphology image of the sample at 550°C in Example 5 of the present invention;

[0031] Figure 4 -b is a 2000 times fracture morphology image of the sample at 650°C in Example 5 of the present invention;

[0032] Figure 4 -c is a 2000 times fracture morphology image of the sample at 700°C in Example 5 of the present invention;

[0033] Figure 4 -d is a 2000 times fracture morphology image of the sample at 750°C in Example 5 of the present invention;

[0034] Figure 4 -e is a 2000 times fracture morphology image of the sample at 800°C in Example 5 of the present invention;

[0035] Figure 4 -f is a 2000 times fracture morphology image of the sample at 950°C in Example 5 of the present invention;

[0036] Figure 5 The engineering stress-strain curves of the samples of the present invention under different heat treatment modes;

[0037] Figure 6 The tensile fracture morphology of the sample of the present invention under different heat treatment methods;

[0038] Figure 7 The engineering stress-strain curves of the samples of the present invention under different heat treatment modes;

[0039] Figure 8 The tensile fracture morphology of the sample of the present invention under different heat treatment methods;

[0040] Fig. 9 -a is a 150-fold metallographic image of Example 2 of the present invention;

[0041] Fig. 9 -b is a 250-fold metallographic image of Example 2 of the present invention;

[0042] Fig. 9 -c is a 500-fold metallographic image of Example 2 of the present invention;

[0043] Fig. 9 -d is a 150-fold metallographic image of Example 3 of the present invention;

[0044] Fig. 9 -e is a 250-fold metallographic image of Example 3 of the present invention;

[0045] Fig. 9 -f is a 500-fold metallographic picture of Example 3 of the present invention;

[0046] Fig. 9-g is a 150-fold metallographic image of Example 4 of the present invention;

[0047] Fig. 9 -h is a 250-fold metallographic image of Example 4 of the present invention;

[0048] Fig.10 The XRD pattern of Example 5 of the present invention;

[0049] Fig.11 XRD pattern of Example 6 of the present invention. DETAILED DESCRIPTION

[0050] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0051] An ultra-high-strength and high-toughness Fe-Mn-Ni alloy and a preparation method thereof, comprising the following steps:

[0052] Step 1, according to the following chemical composition and mass ratio, the mass percentage of the metal powders of Fe, Mn, Ni, and C elements is: Fe 91.2%, Mn 2.8%, Ni 5.7%, C 0.3%, the purity of the metal powders is higher than 99.95%, and the average particle diameter is controlled between 50-100 μm through the screening process;

[0053] The metal powder was mixed by ultrasonic mixing. The ratio of powder mass to deionized water liquid was 10:1. The ultrasonic processor was set to 350W power and 40kHz frequency for 30 minutes of pulse mode treatment to ensure that the powder was fully dispersed. During the treatment, the liquid temperature should be controlled at 50°C to avoid overheating and affect the powder dispersion effect. After the mixing was completed, the medium was separated by natural sedimentation. The powder was left to stand for one day, the powder deposited at the bottom was collected, and the upper clear liquid was absorbed. The powder was placed in an oven to dry and finally dried in an oven at 120°C for 2 hours to ensure that the powder was completely dry and there was no residual liquid.

[0054] Step 2, placing the dried powder in a gas compressor for hot isostatic pressing treatment, melting in a helium gas environment, hot isostatic pressing is carried out in a temperature range of 1000°C-1100°C, a heating rate of 10°C / s, an applied pressure of 120MPa, a pressurizing time of 30 minutes, and a holding time of 2 hours; during the pressurizing process, the temperature and pressure must be evenly transmitted to ensure the densification effect; after the treatment, the temperature is slowly lowered at a cooling rate of 10°C / min to avoid internal stress or cracks, and a Fe-Mn-Ni alloy ingot is obtained, and its grain size and organizational uniformity are detected by optical microscopy and XRD analysis to ensure that the subsequent processing requirements are met;

[0055] The gas compressor can achieve densification of powder materials, elimination of pores and homogenization of microstructure through the uniform transmission of high-temperature and high-pressure inert gas. It can maintain the geometric integrity of the material while applying isotropic pressure, avoid uneven deformation or internal stress, and effectively improve the mechanical properties and reliability of the alloy.

[0056] Step 3, the ingot is kept at 1200°C for 90 minutes to complete the solution treatment. At this temperature, the alloy elements (such as Mn, Ni, C) are fully dissolved into the matrix, and the segregation phenomenon in the cast structure is effectively eliminated. Element segregation often exists in the cast material, which may lead to uneven material properties and affect the quality and reliability in subsequent processing. The solution treatment at 1200°C not only helps to dissolve the alloy elements in the raw materials, but also eliminates the coarse grain structure and makes the material structure more uniform.

[0057] Step 4: hot extrude the solution treated ingot within a temperature range of 900°C to 1000°C to ensure that the alloy has good fluidity and plasticity. The pressure applied during extrusion is 1000Mpa to promote densification and optimize the microstructure. The extrusion speed is controlled at 5mm / s to ensure sufficient deformation without cooling too fast. After extrusion, it should be cooled at a rate of 10°C / min to avoid internal stress or cracks, so as to obtain an ultra-high strength and high toughness Fe-Mn-Ni alloy ingot. By precisely controlling these parameters, the density and mechanical properties of the alloy can be effectively improved.

[0058] An ultra-high-strength and high-toughness Fe-Mn-Ni alloy is prepared by the above-mentioned method for preparing the ultra-high-strength and high-toughness Fe-Mn-Ni alloy.

[0059] Example 1

[0060] In this embodiment, the Fe-Mn-Ni alloy (Fe-2.8Mn-5.7Ni-0.3C) obtained according to the above preparation method was kept at 950°C for 30 minutes, and then a salt bath insulation sample was prepared thereon, and the salt bath temperatures were 250°C, 300°C, 350°C, and 400°C, respectively.

[0061] Comparative Example 1

[0062] In this comparative example, Ni in the Fe-Mn-Ni alloy preparation method is replaced with Al, while other conditions remain unchanged, to obtain a Fe-Mn-Al alloy (Fe-2.8Mn-5.7Al-0.3C), and the alloy is kept at 950°C for 30 min. Salt bath insulation samples are then prepared therefrom, and the salt bath temperatures are 250°C, 300°C, 350°C, and 400°C, respectively.

[0063] Through the comparative experiment of the samples of Example 1 and Comparative Example 1, it is obtained Figure 1The results show that the hardness of Fe-Mn-Ni alloy (Fe-2.8Mn-5.7Ni-0.3C) is significantly higher than that of Fe-Mn-Al alloy (Fe-2.8Mn-5.7Al-0.3C); the two groups of alloys show a trend of first increasing and then decreasing with the increase of salt bath temperature at different salt bath temperatures. Among them, the hardness of both alloys reaches the peak after 300℃ salt bath treatment, showing the best strengthening effect. This difference may be attributed to the solid solution strengthening and stabilization of grain boundaries of Ni element in Fe-Mn-Ni alloy, as well as its more favorable formation of fine martensite or bainite phase at 300℃ salt bath temperature. However, Fe-Mn-Al alloy has a lower overall hardness due to the weak solid solution effect of Al element and limited contribution to high temperature phase transformation.

[0064] Example 2

[0065] In this embodiment, the prepared Fe-Mn-Ni alloy (Fe-2.8Mn-5.7Ni-0.3C) was kept at 900°C for 10 minutes to prepare a salt bath insulation sample. The salt bath temperature was 200°C. The sample was rolled in the salt bath furnace for 20 seconds each time to reduce the thickness by 36%.

[0066] Comparative Example 2

[0067] In this comparative example, Ni in the preparation method of Fe-Mn-Ni alloy is replaced by Al, and other conditions remain unchanged to obtain Fe-Mn-Al alloy (Fe-2.8Mn-5.7Al-0.3C), which is kept at 900°C for 10 minutes to prepare a salt bath insulation sample with a salt bath temperature of 200°C. The sample is rolled in a salt bath furnace for every 20 seconds of rolling to reduce the thickness by 36%.

[0068] Example 3

[0069] In this embodiment, the prepared Fe-Mn-Ni alloy is kept at 800° C. for 40 minutes, then water quenched, tempered at 550° C. for 1 hour, and air-cooled to room temperature.

[0070] Example 4

[0071] In this embodiment, the prepared Fe-Mn-Ni alloy is kept at 900°C for 40 minutes and then air-cooled, kept at 790°C for 40 minutes and then air-cooled, and then kept at 550°C for 1 hour and then water-quenched.

[0072] Through the comparative test of Example 2 and Comparative Example 2, it is obtained Figure 2The results show that the hardness of the Fe-Mn-Ni alloy (Fe-2.8Mn-5.7Ni-0.3C) is 379.2HV, which is significantly higher than the hardness of the Fe-Mn-Al alloy (Fe-2.8Mn-5.7Al-0.3C) of 322.1HV. This significant difference is mainly attributed to the solid solution strengthening effect of Ni in the Fe-Mn-Ni alloy and the promotion of Ni on phase transformation behavior and grain refinement during rolling. Ni can effectively stabilize austenite, form a more uniform deformation structure, and distribute fine strengthening phases in the grain boundaries and matrix, thereby significantly improving the hardness and mechanical properties of the alloy. In addition, the rolling process under 200℃ salt bath conditions further strengthens the performance of the Fe-Mn-Ni alloy, promotes the stabilization of retained austenite and the formation of fine martensite phase, and further improves its hardness.

[0073] In contrast, the hardness performance of Fe-Mn-Al alloys is obviously insufficient, which is mainly attributed to the weak solid solution strengthening effect of Al element and its limited contribution to phase transformation behavior. During the rolling process, Al did not significantly improve grain refinement or structural stability, nor did it effectively promote the formation of strengthening phases, resulting in low hardness and comprehensive performance. At the same time, Al element's ability to regulate phase transformation temperature is not as good as Ni, and it cannot form an equally stable and refined microstructure, which further limits the performance improvement of Fe-Mn-Al alloys.

[0074] Although Fe-Mn-Ni alloys show relatively high hardness in the rolling process under 200°C salt bath conditions, their performance still has room for further optimization. By increasing the heat treatment temperature or adjusting the heat treatment time, the grain structure and phase composition of the alloy can be significantly improved, and the toughness, fatigue resistance and comprehensive mechanical properties can be further improved.

[0075] By analyzing the microstructures of Examples 2, 3, and 4 under different heat treatment processes (such as Fig. 9 As shown), the following conclusions are drawn:

[0076] Metallographic pictures of Example 2 Fig. 9 -a, Fig. 9 -b, Fig. 9 -c, its microstructure is mainly composed of fine lath-shaped martensite, accompanied by a small amount of residual austenite. Dynamic recrystallization significantly refines the grains and forms a uniform deformed structure. This organizational structure has excellent strengthening effect, significantly improves hardness, and exhibits high mechanical properties. However, this process takes strengthening as the main goal. Although the hardness is high, the toughness and fatigue resistance are relatively insufficient. There is room for improvement when the comprehensive performance requirements are high.

[0077] Metallographic images of Example 3 Fig. 9 -d, Fig. 9 -e, Fig. 9 -f, its microstructure is tempered martensite and partially refined ferrite phase. The tempering process effectively releases the quenching residual stress and further enhances the hardness through the precipitation of carbides. However, the softening of some strengthening phases during the tempering process leads to limited performance improvement. In addition, the increase in the relative proportion of tempered ferrite makes the overall organization tend to balance, but the optimization between comprehensive strength and toughness is still not as good as more advanced heat treatment processes.

[0078] Metallographic images of Example 4 Fig. 9 -g, Fig. 9 In Figure -h, the microstructure is mainly ferrite, with a small amount of dispersed precipitated carbides distributed locally. The process achieves an improvement in comprehensive performance through carbide precipitation and microstructure stabilization. However, although the ferrite-based structure has good toughness and plasticity, its strength and hardness are lower than the ideal effect. This shows that the process is suitable for application scenarios with high requirements for toughness but relatively low strength requirements.

[0079] Although both Examples 3 and 4 have improved organizational stability, their comprehensive performance is still inferior to the strengthened microstructure dominated by fine lath martensite in Example 2. This indicates that it is still necessary to further optimize the heat treatment process (such as adjusting the heating temperature, holding time or combining multiple steps) to balance hardness, strength and toughness and fully tap the performance potential of Fe-Mn-Ni alloys.

[0080] Example 5

[0081] In this embodiment, the prepared Fe-Mn-Ni alloy is kept at 550°C, 650°C, 700°C, 750°C, 800°C, and 950°C for 10 min, respectively, and air-cooled to room temperature. The ingot is kept in a 150°C salt bath furnace for 30 min and air-cooled to room temperature.

[0082] Example 6

[0083] In this embodiment, the prepared Fe-Mn-Ni alloy is kept at 950°C for 10 minutes and air-cooled to room temperature. The ingot is then kept in a salt bath furnace at 0°C, 150°C, 200°C, 250°C, and 300°C for 30 minutes and air-cooled to room temperature.

[0084] The treated samples in Examples 5 and 6 were subjected to a tensile test, and the tensile test was conducted at a tensile rate of 0.5 mm / min. According to the tensile test results of Example 5, Figure 3It can be seen that: the fracture morphology shows that with the increase of heat treatment temperature, the dimples gradually increase and deepen, showing the enhancement of plastic fracture characteristics; after 550℃ salt bath treatment, the fracture dimples are shallow and unevenly distributed, indicating that the material has weak plastic deformation ability. It is speculated that the low temperature fails to effectively promote the stability of the austenite phase or the precipitation phase is not fully dissolved, resulting in insufficient matrix microstructure performance; when treated at 750℃ salt bath, the dimples are deep and evenly distributed, indicating that the material has achieved the best microstructure regulation effect at this temperature, sufficient Ni and Mn solid solution strengthening and partial decomposition of carbides to form a stable FCC austenite phase, thereby improving toughness and plasticity; after treatment at 800℃ and above, although the dimples further increase, the performance decreases, which is speculated to be related to grain coarsening, grain boundary weakening and possible element segregation or grain boundary precipitation phase.

[0085] Combination Figure 3 The stress-strain curve of Figure 4 From the microscopic morphology, the changes of the two are consistent. When treated at 550℃, the material showed the lowest yield strength and ductility, and the fracture mode tended to be brittle; the 750℃ treatment showed the highest yield strength and ductility, which was consistent with the dimple morphology characteristics, indicating that the homogenization of the organization and the stability of the FCC phase were optimal at this temperature, giving the material excellent comprehensive mechanical properties; although the ductility was retained at 800℃ and above, the yield strength decreased, indicating that the excessively high temperature weakened the grain boundary strengthening effect; On the whole, the 750℃ salt bath 150℃ treatment can achieve the best balance between material strength and plasticity, which is the preferred temperature range for heat treatment of the alloy, while too low or too high temperatures are not conducive to performance improvement.

[0086] In Example 6, the tensile fracture and mechanical properties of Fe-2.8Mn-5.7Ni-0.3C alloy after austenitization at 950℃ were analyzed by different cooling methods (air cooling to room temperature, salt bath 150℃, salt bath 250℃, salt bath 300℃), revealing the significant effect of cooling path on organizational stability and mechanical properties. From the fracture morphology analysis, as shown in Figure 6 As shown in Figures a, b, c, and d, the dimple morphology changes slightly under different cooling conditions, but the salt bath treatment makes the dimple slightly deeper and more evenly distributed, and no significant cracks are observed. This indicates that there may be high residual stress under rapid cooling conditions, while the salt bath slow cooling effectively releases the internal stress and improves the fracture toughness. When air-cooled to room temperature, Figure 6 As shown in a, the dimples are moderate in depth and evenly distributed. The high residual stress from rapid cooling helps to strengthen the material strength, but may reduce toughness. Figure 6 As shown in b, the dimples are slightly deeper and evenly distributed, reflecting the stability of the austenite phase and the effective release of internal stress; under the conditions of 250℃ and 300℃ in the salt bath, Figure 6As shown in c and d, the dimple depth does not change significantly, but the tissue uniformity is further improved, indicating that the high-temperature salt bath helps to further reduce stress concentration, but may cause local softening.

[0087] The stress-strain behavior under Example 6 is as follows Figure 5 As shown in the figure, the yield strength gradually decreases with the increase of salt bath temperature, while the strain remains relatively stable. The highest yield strength can be obtained by air cooling to room temperature. Rapid cooling promotes grain refinement, but the toughness of the material may be reduced due to residual stress. The salt bath treatment at 150℃ shows better comprehensive properties. The yield strength is slightly lower than that of air cooling, but the elongation is significantly improved, indicating that slow cooling effectively avoids the negative effects of high residual stress and improves plasticity while maintaining high strength; under the salt bath treatment conditions of 250℃ and 300℃, the yield strength is further reduced, and the strain change is not significant. It is speculated that due to the further growth of grains at higher temperatures, the strengthening effect is weakened, and the stability of austenite is reduced. In summary, after austenitization treatment at 950℃, cooling at 150℃ in a salt bath can achieve the best balance between strength and toughness, while too high a salt bath temperature will lead to a decrease in strength.

[0088] Example 7

[0089] In this embodiment, the smelted Fe-Mn-Ni alloy is kept at 750°C for 10 minutes, air-cooled to room temperature, and then the ingot is kept in a salt bath furnace at 150°C, 200°C, 250°C, and 300°C for 30 minutes, respectively, and air-cooled to room temperature.

[0090] The sample treated in Example 7 was subjected to a tensile test, and the tensile fracture morphology (such as Figure 8 as shown) and mechanical properties (as Figure 7The results of the analysis of the heat treatment time and the mechanical properties of the material (shown in Figure 2) reveal the significant effect of the heat treatment time on the microstructure and mechanical properties of the material. The fracture morphology shows that with the extension of the salt bath time, the dimples gradually become larger and deeper, but at the same time, the number of cracks increases and the size increases, reflecting the complex effect of organizational evolution on the plasticity and toughness of the material. After the salt bath treatment at 150°C, the material exhibits uniform dimple characteristics with moderate depth. Combined with the stress-strain curve, it can be seen that its yield strength and elongation are both optimal, indicating that the material structure is uniform under this condition, the FCC austenite phase is stable, and the grain boundaries are not significantly weakened. After the salt bath treatment at 200°C, the dimples deepen but the number decreases, accompanied by local cracks. The yield strength is close to that of the 150°C treatment, but the strain is significantly reduced, indicating that local precipitation may occur at the grain boundaries or subgrain boundaries, affecting the plasticity of the material. When treated in a salt bath at 250°C, the dimples increased significantly and were accompanied by larger cracks. The fracture morphology showed brittle fracture characteristics, and the yield strength and ductility in the stress-strain curve decreased significantly. It is speculated that this is due to the increase in grain boundary precipitation phases or grain coarsening, which led to grain boundary weakening and plastic degradation. After treatment in a salt bath at 300°C, the dimples tended to be stable and the ductility recovered, but the yield strength decreased further, which may be related to the further growth of grains in the organization and precipitation at grain boundaries. Therefore, it is confirmed again that the moderate treatment time of the 750°C salt bath and 150°C treatment (i.e., "keeping in a muffle furnace at 750°C for 10 minutes and then air cooling to room temperature in step 5, keeping in a salt bath furnace at 150°C for 30 minutes and then air cooling to room temperature) effectively avoids the adverse effects of increased grain boundary precipitates and grain coarsening, while achieving balanced optimization of strength and toughness.

[0091] like Fig.10 As shown in the figure, the diffraction peaks of all samples correspond to the face-centered cubic (FCC) structure, with the main peak located at the (111) crystal plane, accompanied by (200) and (220) secondary diffraction peaks. In the sample treated at low temperature (550℃), the (111) peak is significantly broadened, indicating that the grain size is small and there are more crystal defects. At the same time, the wider diffraction peak may indicate that the microstress inside the lattice is large. As the heat treatment temperature increases to 950℃, the diffraction peak gradually becomes sharper, the intensity is significantly enhanced, and the peak position is slightly shifted to the left, indicating that the lattice constant increases, which may be caused by thermal expansion and improved crystal quality. The clarity of the secondary diffraction peak further verifies that high temperature treatment improves the orderliness of the crystal.

[0092] The treatment in a salt bath at 150°C played a certain role in removing the oxide layer on the crystal surface of the sample and releasing stress. The phase composition did not show the appearance of obvious new phases, indicating that the stability of the single FCC phase structure was maintained within the heat treatment temperature range used. Comprehensive analysis showed that the heat treatment temperature had a significant effect on the grain size, phase structure stability and internal stress.

[0093] According to Example 6, Fig.11The XRD patterns of Fe-Mn-Ni alloys after annealing at 950℃, treatment with different salt bath temperatures (200℃, 250℃, 300℃) and air cooling were analyzed. The results showed that all samples retained the face-centered cubic (FCC) phase structure. The (111) peak of the air-cooled sample was wider and less intense, indicating that the grains were smaller and the microstress was larger. With the increase of the salt bath temperature, the (111) peak became sharper and the intensity increased, the grain size increased, the internal stress decreased, and the crystal quality improved. The secondary diffraction peaks (200) and (220) were clearer in the salt bath cooled samples, proving that the salt bath temperature helps to improve the crystal order. Overall, salt bath cooling can effectively reduce crystal defects than air cooling.

[0094] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy, characterized in that: The following steps are involved: Step 1, according to the following chemical composition and mass ratio, the mass percentage of the metal powders of Fe, Mn, Ni and C elements is: Fe 91.2%, Mn 2.8%, Ni 5.7%, C 0.3%, ultrasonic mixing method is used for mixing, natural sedimentation method is used for separating the medium, and the powder is placed in an oven for drying; Step 2: placing the dried powder in a gas compressor for hot isostatic pressing, and smelting the powder in a helium gas environment to obtain a Fe-Mn-Ni alloy ingot; Step 3, subjecting the ingot to a solution treatment; Step 4, hot extruding the solution treated ingot to obtain an alloy ingot; Step 5: The alloy ingot after hot extrusion treatment is kept in a muffle furnace at 750° C. for 10 minutes and then air-cooled to room temperature; it is kept in a salt bath furnace at 150° C. for 30 minutes and then air-cooled to room temperature to obtain an ultra-high strength and high toughness Fe-Mn-Ni alloy.

2. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 1, characterized in that: In the step 1, the purity of Fe, Mn, Ni and C powders is higher than 99.95%.

3. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 2, characterized in that: In the step 1, the average particle diameter of the Fe, Mn, Ni and C metal powders is controlled to be between 50 and 100 μm through a screening process.

4. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 1, characterized in that: In the step 1, when mixing by ultrasonic mixing, the ratio of powder mass to deionized water liquid is 10:1, the ultrasonic processor is set to 350W power and 40kHz frequency, and the pulse mode treatment is performed for 30 minutes. The liquid temperature should be controlled at 50°C. After the mixing is completed, the powder is allowed to stand for one day by natural sedimentation method, the powder deposited at the bottom is collected, the upper clear liquid is absorbed, and finally dried in an oven at 120°C for 2 hours.

5. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 3, characterized in that: In the step 2, hot isostatic pressing is carried out in a temperature range of 1000°C-1100°C, a heating rate of 10°C / s, an applied pressure of 120MPa, a pressing time of 30 minutes, and a holding time of 2 hours; during the pressing process, the temperature and pressure need to be evenly transmitted to ensure the densification effect; after the treatment, the temperature is slowly lowered at a cooling rate of 10°C / min to finally obtain a Fe-Mn-Ni alloy ingot.

6. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 5, characterized in that: The grain size and structural uniformity of the Fe-Mn-Ni alloy ingot obtained in step 2 are detected by optical microscopy and XRD analysis to ensure that the subsequent processing requirements are met.

7. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 1, characterized in that: In step 3, the ingot is kept at 1200° C. for 90 minutes to complete the solution treatment.

8. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 1, characterized in that: In the step 4, the alloy ingot after the solution treatment is hot extruded in a temperature range of 900° C. to 1000° C., the pressure applied during the extrusion is 1000 MPa, and the extrusion speed is controlled at 5 mm / s.

9. The method for preparing an ultra-high strength and high toughness Fe-Mn-Ni alloy according to claim 8, characterized in that: In the step 4, after the extrusion is completed, cooling is performed at a rate of 10° C. / min.

10. An ultra-high strength and high toughness Fe-Mn-Ni alloy, characterized in that: The alloy is prepared by the method for preparing the ultra-high-strength and high-toughness Fe-Mn-Ni alloy described in any one of claims 1 to 9.

Citation Information

Patent Citations

  • Ceramimetallurgical high-wear-resistance high-toughness cold work die steel and preparation method thereof

    CN103194685A

  • Preparation method of thermal bimetal component layer Fe-Ni-Mn alloy

    CN110699591A

  • Near-net forming preparation method of ferrite-based alloy complex-shape part

    CN118577791A

  • JP1974097710A

  • Sintered iron alloy

    JP1981062951A